HM015k, a Novel Silybin Derivative, Multi-Targets Metastatic Ovarian Cancer Cells and Is Safe in Zebrafish Toxicity Studies - Amawi, Haneen; Hussein, Noor A.; Karthikeyan, Chandrabose; Manivannan, Elangovan; Wisner, Alexander; Williams, Frederick E.; Samuel, Temesgen; Trivedi, Piyush; Ashby, Charles R.; Tiwari, Amit K. (Frontiers in Pharmacology, 2017)
This study was designed to determine the in vitro mechanisms by which the novel silybin derivative, (E)-3-(3-(benzyloxy) phenyl)-1-(4-hydroxyphenyl)prop-2-en-1-one (HM015k or 15k), produces its anticancer efficacy in ovarian cancer cells. Compound 15k induced apoptosis in ovarian cancer cells in a time-dependent manner by significantly upregulating the expression of Bax and Bak and downregulating the expression of the Bcl2. Interestingly, 15k induced the cleavage of Bax p21 into its more efficacious cleaved form, Bax p18. In addition, caspase 3 and caspase 9 were cleaved to their active forms, inducing the cleavage of poly ADP ribose polymerase (PARP) and β-catenin. Furthermore, in OV2008 cells, 15k induced significant cleavage in nuclear β-catenin to primarily inactive fragments of lower molecular weight. Furthermore, 15k reversed the metastatic potential of OV2008 cells by inhibiting their migration and invasiveness. The mesenchymal phenotype in OV2008 was reversed by 15k, causing cells to be rounder with epithelial - like phenotypes. The 15k-induced reversal was further confirmed by significant upregulation of the E-cadherin expression, an epithelial marker, while N-cadherin, a mesenchymal marker, was downregulated in OV2008 cells. Compound 15k inhibited the expression of the oncogenic c-Myc protein, downregulated proteins DVL3 and DVL2 and significantly upregulated cyclin B1. Also, 15k significantly downregulated the expression levels of ABCG2 and ABCB1 transporters in resistant ABCG2 overexpressing H460/MX20 and resistant ABCB1 overexpressing MDCK/MDR1 cells, respectively. Finally, 15k was safe in zebrafish in vivo model at concentrations up to 10 µM and induced no major toxicities in cardiac, morphology and swimming position parameters. Overall, 15k is a multi-targeted inhibitor with an efficacy against metastatic and resistant ovarian cancer. Future in vivo studies will be conducted to determine the efficacy of 15k in tumor-bearing animals.